Charting the landscape of the environmental exposome. Issue 4 (2nd September 2022) - Wei, Xin; Huang, Zinuo; Jiang, Liuyiqi; Li, Yueer; Zhang, Xinyue; Leng, Yuxin; Jiang, Chao
Abstract: The exposome depicts the total exposures in the lifetime of an organism. Human exposome comprises exposures from environmental and humanistic sources. Biological, chemical, and physical environmental exposures pose potential health threats, especially to susceptible populations. Although still in its nascent stage, we are beginning to recognize the vast and dynamic nature of the exposome. In this review, we systematically summarize the biological and chemical environmental exposomes in three broad environmental matrices—air, soil, and water; each contains several distinct subcategories, along with a brief introduction to the physical exposome. Disease‐related environmental exposures are highlighted, and humans are also a major source of disease‐related biological exposures. We further discuss the interactions between biological, chemical, and physical exposomes. Finally, we propose a list of outstanding challenges under the exposome research framework that need to be addressed to move the field forward. Taken together, we present a detailed landscape of environmental exposome to prime researchers to join this exciting new field. Abstract : We describe the biological and chemical components of the environmental exposomes in three major environmental matrices that are highly relevant to human and social‐economical health—air, soil, and water. We discuss how different exposome components can interact with each other. Finally, we propose a list of outstanding challenges to be tackled to push the field forward. Highlights: The biological and chemical exposures in air, soil, and water were summarized and united under the exposome framework. Biological, chemical, and physical exposures are dynamically interweaved. A list of outstanding challenges was proposed to be tackled to push the field forward.